THE SUITABILITY OF THE BMY2 AND WAXY GENES AND INTERNAL TRANSCRIBED SPACERS OF RRNA AS MARKERS FOR STUDYING GENETIC VARIABILITY IN ELYMUS SPECIES - N. A. Shmakov; D. A. Afonnikov; P. A. Belavin; A. V. Agafonov (Вавиловский журнал генетики и селекции, 2015)
Elymus L. is a genus of the Poaceae family, which includes only polyploid species. It is widespread over all continents, with at least half of the species occurring in Asia, and this continent is considered to be its motherland. However, the diversity, genetic characteristics, and evolutionary interactions among Elymus species of some regions of Asia are still vague, and the Far East of Russia is one of such territories. Thus, investigation of evolutionary relations among species of Far East and Kamchatka is promising. In this work, several sequences of two nuclear genes and rDNA Internal Transcribed Spacers annotated in databases are analyzed. Nuclear genes sequences are shown to be more useful in building phylogeny at the interspecies level. Also, a region of the nuclear gene waxy is shown to vary among different haplomes. This variation makes it useful in investigating the genome constitutions of novel Elymus species. Finally, systematical status of E. kamczadalorum as a species was proven valid.